1986
DOI: 10.2337/diab.35.9.951
|View full text |Cite
|
Sign up to set email alerts
|

Further Evidence Implicating Diacylglycerol Generation and Protein Kinase C Activation in Agonist-Induced Increases in Glucose Uptake: Insulin-Like Effects of Phenylephrine in BC3H-1 Myocytes

Abstract: We have previously suggested that insulin effects on 2-deoxyglucose (2-DOG) uptake in BC3H-1 myocytes are due to increases in de novo phospholipid synthesis, diacylglycerol generation, and protein kinase C activation. To test this hypothesis further, we examined the effects of phenylephrine, an agonist that increases diacylglycerol and protein kinase C activity through phospholipase C activation. As evidence for phospholipase activation in BC3H-1 myocytes, we found that phenylephrine increased acute 32PO4 inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1987
1987
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Moreover, it has been documented that α 1 -adrenoceptor agonist, phenylephrine, can activate phospholipase C (PLC) in muscle cells (Farese et al 1986). Incubation with α 1 -adrenoceptor agonist releases inositol-1,4,5-phosphate into the cytosol and increases diacylglycerol (DAG) within membrane in white adipocytes of rats (Faintrenie and Géloén 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it has been documented that α 1 -adrenoceptor agonist, phenylephrine, can activate phospholipase C (PLC) in muscle cells (Farese et al 1986). Incubation with α 1 -adrenoceptor agonist releases inositol-1,4,5-phosphate into the cytosol and increases diacylglycerol (DAG) within membrane in white adipocytes of rats (Faintrenie and Géloén 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Incubation with α 1 -adrenoceptor agonist releases inositol-1,4,5-phosphate into the cytosol and increases diacylglycerol (DAG) within membrane in white adipocytes of rats (Faintrenie and Géloén 1998). The accumulation of DAG and Ca 2+ as a result of activation of PLC causes the activation of protein kinase C (PKC; Farese et al 1986). Mediation of PLC-PKC pathway in the activation of α 1 -adrenoceptor was also characterized in C 2 C 12 cells depending on the blockade of caffeic acid-stimulated 2-DG uptake by the inhibitors specific for PLC or PKC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One piece of evidence supporting this hypothesis was the observation that phorbol esters, which can substitute for diacylglycerol as an activator of protein kinase C, show insulin-like effects in isolated adipocytes (Van de Werve et al, 1985;Kirsch et al, 1985) as well as in myocytes in culture (Farese et al, 1985). Whereas in the myocyte culture diacylglycerol and phorbol esters are able to elicit the full insulin response (Farese et al, 1986), only a partial insulin-like effect, usually not more than 30 % of the maximal insulin effect, can be induced in isolated rat 10 20…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that they include activation ofthe intrinsic insulin-receptor kinase (Kasuga et al, 1983) and phosphorylation of cellular proteins (Hiring et al, 1987;White et al, 1985;Machicao et al, 1987), followed by as yet unknown intermediary steps, finally resulting in a translocation of glucose carrier sites from intracellular membranes to the plasma membrane (Wardzala et al, 1978;Cushman & Wardzala, 1980;Karnieli et al, 1981). Several lines of evidence have suggested that the steps linking insulin-receptor kinase and activation of the glucose-transport system might involve the phosphatidylinositol cycle (K6pfer- Hobelsberger & Wieland, 1984;Kirsch et al, 1985;Van de Werve et al, 1985;Nishizuka, 1986), release of diacylglycerol (Farese et al, 1985) and activation of protein kinase C (Farese et al, 1986). This speculation is partially based on the observation that tumour-promoting phorbol esters, which can substitute for diacylglycerol as stimulators of protein kinase C, are able to Abbreviation used: TPA, 12-0-tetradecanoylphorbol 13-acetate.…”
Section: Introductionmentioning
confidence: 99%